XMLBeans the best of both worlds. - Seth, Hitesh
"Java and XML-portable code and portable data." Even though this saying has been around since Java developers began using XML, developers have always faced a general XML programming-related productivity problem : manipulating XML content is rather different from manipulating Java objects.